Preparation of BMP-2/PDA-BCP Bioceramic Scaffold by DLP 3D Printing and its Ability for Inducing Continuous Bone Formation - Yang, Ziyang; Xie, Li; Zhang, Boqing; Zhang, Gang; Huo, Fangjun; Zhou, Changchun; Liang, Xi; Fan, Yujiang; Tian, Weidong; Tan, Yinghui (Frontiers in Bioengineering and Biotechnology, 2022)
Digital light processing (DLP)-based 3D printing is suitable to fabricate bone scaffolds with small size and high precision. However, the published literatures mainly deal with the fabrication procedure and parameters of DLP printed bioceramic scaffold, but lack the subsequent systematic biological evaluations for bone regeneration application. In this work, a biphasic calcium phosphate (BCP) macroporous scaffold was constructed by DLP-based 3D printing technique. Furthermore, bone morphogenetic protein-2 (BMP-2) was facilely incorporated into this scaffold through a facile polydopamine (PDA) modification process. The resultant scaffold presents an interconnected porous structure with pore size of ~570 μm, compressive strength (~3.6 MPa), and the self-assembly Ca-P/PDA nanocoating exhibited excellent sustained-release property for BMP-2. Notably, this BMP-2/PDA-BCP scaffold presents favorable effects on the adhesion, proliferation, osteogenic differentiation, and mineralization of bone marrow stromal cells (BMSCs). Furthermore, in vivo experiments conducted on rats demonstrated that the scaffolds can induce cell layer aggregation adjacent the scaffolds and continuous new bone generation within the scaffold. Collectively, this work demonstrated that the BMP-2/PDA-BCP scaffold is of great potential to treat small craniofacial bone defects in demand of high accuracy.